2017
DOI: 10.1089/aid.2016.0319
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Heightened HIV Antibody Responses in Postpartum Women as Exemplified by Recent Infection Assays: Implications for Incidence Estimates

Abstract: Laboratory assays that identify recent HIV infections are important for assessing impacts of interventions aimed at reducing HIV incidence. Kinetics of HIV humoral responses can vary with inherent assay properties, and between HIV subtypes, populations, and physiological states. They are important in determining mean duration of recent infection (MDRI) for antibody-based assays for detecting recent HIV infections. We determined MDRIs for multi-subtype peptide representing subtypes B, E and D (BED)-capture enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The mean window period we calculated for the current LAg algorithm in this study (142 days) was nearly identical to the 2 year MDRI for this algorithm that was calculated by the Consortium for the Evaluation of the Performance of HIV Incidence Assays (CEPHIA; 141 days, 95% CI: 123 to 160 days) ; the CEPHIA estimate was based on a sample set that was not limited to subtype C samples. A recent report cited a much lower MDRI for the LAg‐Avidity assay (101 days) .…”
Section: Discussionmentioning
confidence: 99%
“…The mean window period we calculated for the current LAg algorithm in this study (142 days) was nearly identical to the 2 year MDRI for this algorithm that was calculated by the Consortium for the Evaluation of the Performance of HIV Incidence Assays (CEPHIA; 141 days, 95% CI: 123 to 160 days) ; the CEPHIA estimate was based on a sample set that was not limited to subtype C samples. A recent report cited a much lower MDRI for the LAg‐Avidity assay (101 days) .…”
Section: Discussionmentioning
confidence: 99%
“…During the past decade, several laboratory incidence assays have been conducted, and the HIV-1 BED-capture-enzyme immunoassay (BED-CEIA) being the most commonly used for HIV surveillance. The method is an IgG capture enzyme immunoassay used to detect and distinguish recent from long-term HIV-1 infections, and has been used widely to estimate HIV incidence in many areas, both in China [ 10 – 14 ] and outside of China [ 15 19 ]. While limited investigation was found to examine the trend of HIV incidence and factors causing the trend, especially in a metropolitan of huge mobile population for a long period.…”
Section: Introductionmentioning
confidence: 99%
“…For example, we found two studies done using samples collected from the Zimbabwe Vitamin A for Mothers and Babies Trial, where postpartum women and their new-borns were recruited and followed, to observe effects of maternal and/or neonatal vitamin A in reducing HIV transmission, comorbidities, and child mortality. 54 , 55 Both studies found that MDRI and FRR estimates were lower compared to other studies. This further demonstrates the need to understand how HIV infection among these key populations affect the use of LAg in identifying recent infections.…”
Section: Resultsmentioning
confidence: 94%